A VAR analysis of the effects of Al-Shabaab's pledge to Al-Qaeda on bombings and fatalities. Issue 3 (2nd September 2021) - Onat, Ismail; Guler, Ahmet; Hsu, Henda Y.; Reyes, Jessica
ABSTRACT: Pledging allegiance to a larger terrorist group is assumed to increase activities of religious terrorist groups because of cooperative relationships and further support. In a competing theory, a pledge to another group is viewed as symbolic to motivate a group's supporters. Taking Al-Shabaab terrorism as a case, the current study tests the extent to which those competing theories are valid for frequencies of bombings and relevant fatalities. Even though Al-Shabaab pledged allegiance to al-Qaeda since 2012, the literature lacks an empirical test of whether or not a significant change occurred in Al-Shabaab's attacks after the pledge. Drawing on data from the Global Terrorism Database results from our vector autoregressive (VAR) analysis indicate that the frequency and lethality of Al-Shabaab's bombing attacks and fatalities did not change significantly in the post-pledge period. The contributions of our findings to the terrorism literature are discussed and policy implications for counterterrorism efforts are considered.